Penghapusan Batas Usia Perkawinan Di Indonesia Dalam Perspektif Hak Asasi Manusia - Ramadhan, Muhammad Syahrul; Saputra, Mohamad Guntur; Khadafi, Muhammad Noer (Universitas Sang Bumi Ruwa Jurai, 2024)
This research discusses the analysis of the elimination of the age limit for marriage in Indonesia from a human rights perspective. The main problem in this research is the rise of early marriage which is marked by the increasing demand for marriage dispensations as well as the disapproval of several community groups towards limiting the age of marriage because it is considered to be contrary to the theological and cultural aspects of Indonesian society. The aim of this research is to gain a deeper understanding regarding the elimination of the age limit for marriage in Indonesia from a human rights perspective for the common good. This type of research is library research and a normative legal research approach which focuses on the use of secondary data sources such as the Koran, hadith, books, journals, statutory regulations, court decisions, and so on. The results of this research indicate that the marriage age limit regulations in Indonesia are not in line with human rights values because they marginalize citizens' rights to carry out the religious teachings they believe in in determining their lives. The implementation of the marriage age limit regulations also creates problems in the juridical, sociological (cultural) and theological aspects in Indonesia.